TYPES AND APPLICATION OF PHARMACEUTICAL NANOTECHNOLOGY: A REVIEW - SARVAN; VASHISTH, HEMANT (International Journal of Current Pharmaceutical Research, 2023)
The already enormous health industry will continue to expand as baby boomers begin to enter retirement. Pharmaceutical companies will create new technologies in response to patient expectations, given the size of the customer base and the increasing demand. As pharmaceuticals get more complex and hazardous, new distribution strategies are needed to get them to the correct areas of the body. As a result, well-known pharmaceutical companies are utilising cutting-edge methodologies and technology. One of the most comprehensive technologies is pharmaceutical nanotechnology. Pharmaceutical nanotechnology offers new opportunities, tools, and breadth that are expected to have a big influence on a lot of areas of illness diagnosis and treatment. Pharmaceutical nanotechnology has opportunities to improve materials and medical technology as well as to contribute to the advancement of technology in fields where more seasoned and conventional technologies may be nearing their limits. In conclusion, recent developments, the commercialization of several pharmaceutical nano-tools, and the rising interest of academics, governments, and corporations ensure that nano-based drug delivery systems in the near future have immense potential and range.